1996
DOI: 10.1183/09031936.96.09091795
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an auto-nCPAP device based on snoring detection

Abstract: E Ev va al lu ua at ti io on n o of f a an n a au ut to o--n nC CP PA AP P d de ev vi ic ce e b ba as se ed d o onWe observed that a single night of auto-nCPAP improved the apnoea/hypnoea index (AHI) (12±21 vs 51±31 disordered breathing events·h -1 of sleep (mean±SD)), the awakening-arousal index (13±20 vs 40±26 arousals·h -1 of sleep), and duration of slow wave sleep (102±49 vs 71±56 min) but not of rapid eye movement (REM) sleep (55±31 vs 64±38 min). Auto-nCPAP was effective (apnoea/hypopnoea and arousal ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 23 publications
1
27
0
4
Order By: Relevance
“…The authors recently conducted a clinical study of an auto-nCPAP device (rapid eye movement (REM)zauto) that was the precursor of the Goodknight 418A and had similar sensitivity for snoring detection (unpublished data). It was found that this device induced no detrimental pressure increases [7,8]. Moreover, in one of the 15 patients, who was described by their bed partner as an almost continuous snorer, this auto-nCPAP device failed to detect snoring because the sound was not loud enough [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors recently conducted a clinical study of an auto-nCPAP device (rapid eye movement (REM)zauto) that was the precursor of the Goodknight 418A and had similar sensitivity for snoring detection (unpublished data). It was found that this device induced no detrimental pressure increases [7,8]. Moreover, in one of the 15 patients, who was described by their bed partner as an almost continuous snorer, this auto-nCPAP device failed to detect snoring because the sound was not loud enough [7].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that this device induced no detrimental pressure increases [7,8]. Moreover, in one of the 15 patients, who was described by their bed partner as an almost continuous snorer, this auto-nCPAP device failed to detect snoring because the sound was not loud enough [7]. This result was confirmed by a study reported in abstract form [9], in which snoring was recorded by a stethoscope secured to the trachea in 13 patients who used the precursor of the Goodknight 418A.…”
Section: Discussionmentioning
confidence: 99%
“…Some ventilators designed for home NIMV are using a single inspirationexpiration circuit with a connector which permits venting of expiratory gas towards the atmosphere between the mask and the circuit. However, using such a system, a significant rebreathing has been demonstrated [54][55][56] which can be relevant clinically in patients with high minute ventilation as it may be observed in those with HRF. Therefore in patients having HRF, it is warmly recommended to use a nonrebreathing valve and a separate circuit for expiration.…”
Section: The Exhalation Devicementioning
confidence: 99%
“…This is an important technological issue that has been recently discussed [54][55][56]. Some ventilators designed for home NIMV are using a single inspirationexpiration circuit with a connector which permits venting of expiratory gas towards the atmosphere between the mask and the circuit.…”
Section: The Exhalation Devicementioning
confidence: 99%
“…In that study, slow wave sleep values were normal in middle-aged nonapnoeic snorers with an arousal index of less than 10 events·h -1 (mean 7±2 events·h -1 ), but were abnormal in those with an arousal index of more than 10 events·h -1 (mean 15±5 events·h -1 ). In addition, in another recent study, we observed that successfully treated sleep apnoea syndrome (SAS) patients had less than 10 short EEG arousals·h -1 during sleep [25]. These findings show that when we used the ASDA criteria in our laboratory, arousals occurring at a rate of more than 10 events·h -1 significantly affect the architecture of nocturnal sleep.…”
Section: Discussionmentioning
confidence: 53%